2020
DOI: 10.1038/s41598-020-61876-5
|View full text |Cite
|
Sign up to set email alerts
|

Piscidin-1 Induces Apoptosis via Mitochondrial Reactive Oxygen Species-Regulated Mitochondrial Dysfunction in Human Osteosarcoma Cells

Abstract: Osteosarcoma (OSA) is the most common type of cancer that originates in the bone and usually occurs in young children. OSA patients were treated with neoadjuvant chemotherapy and surgery, and the results were disappointing. Marine antimicrobial peptides (AMPs) have been the focus of antibiotic research because they are resistant to pathogen infection. Piscidin-1 is an AMP from the hybrid striped bass (Morone saxatilis × M. chrysops) and has approximately 22 amino acids. Research has shown that piscidin-1 can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…The Cu 2+ -bound peptides did not exhibit this strong level of cytotoxicity on normal MRC-5 (lung) fibroblast cells (Fig. S1 C), in agreement with the data previously obtained for apo-P1 on MRC-5, HGF-1 (gingival) and OMF (mucosal) fibroblast cells 39 , 78 . Higher selectivity of the cationic peptides for cancer cells is very likely related to different chemical conditions of their membrane environment, as explained in the introduction.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The Cu 2+ -bound peptides did not exhibit this strong level of cytotoxicity on normal MRC-5 (lung) fibroblast cells (Fig. S1 C), in agreement with the data previously obtained for apo-P1 on MRC-5, HGF-1 (gingival) and OMF (mucosal) fibroblast cells 39 , 78 . Higher selectivity of the cationic peptides for cancer cells is very likely related to different chemical conditions of their membrane environment, as explained in the introduction.…”
Section: Resultssupporting
confidence: 91%
“…Our study focused on showing that metallation enhances the cytotoxic effects of piscidins 1 and 3 on cancer cells and explaining this effect through a detailed characterization of peptide-lipid interactions. As a next step, it will be important to determine whether the mechanism of cell death by P1 and P3 bound to Cu 2+ features apoptosis, as previously shown for apo-P1 39 , 78 . For instance, it would be insightful to use cell-based assays to determine whether the Cu 2+ -bound peptides release Cu 2+ intracellularly (e.g., acidic endosomes) resulting in enhanced ROS formation and increased apoptotic effects compared to apo-P1 used at low concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al. 32 reported that Piscidin-1 induced apoptosis via mitochondrial reactive oxygen species-regulated mitochondrial dysfunction in human osteosarcoma cells. 32 Nevertheless, key steps remain to be corroborated, especially those that lead to selective killing of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…32 reported that Piscidin-1 induced apoptosis via mitochondrial reactive oxygen species-regulated mitochondrial dysfunction in human osteosarcoma cells. 32 Nevertheless, key steps remain to be corroborated, especially those that lead to selective killing of cancer cells. How to effectively use mitochondrial dysfunction and its regulatory role in cancer to kill anti-cancer cells in a heterogeneous cell population in tumors is still a promising but not yet fulfilled premise.…”
Section: Discussionmentioning
confidence: 99%